ANALISIS PENGARUH MEREK, KEMASAN, GARANSI DAN PELAYANAN TERHADAP LOYALITAS KONSUMEN AIR MINERAL DALAM KEMASAN AQUA - Nerys Lourensius L. T; TH. A. RADITO (Jurnal Bisnis, Manajemen, dan Akuntansi, 2019)
This study examines the influence of Brands, Packaging, Warranty and Service on Loyalty of Consumers of mineral water in Aqua Packaging at PT. Bintang Sidoraya Yogyakarta. The sampling method in this study, the authors used a non probability sampling method. The sample in this study are customers or consumers at PT. Bintang Sidoraya Yogyakarta, amounting to 100 people. The data research method used in this study is the questionnaire method. While the variables in this study are dependent variables: consumer loyalty (Y) and independent variables: Brand (X1), Packaging (X2), Warranty (X3) and Service (X4). In this study using multiple linear regression analysis to show how far an independent variable affects the dependent variable that can be seen. o test the effect of brand variables on consumer loyalty by comparing significantly the value of t-count = 3.772 with t-table (n = 100 α = 5%) of 1.661 so that it can be concluded t-count > t-table then hypothesis is accepted which means the brand has an influence on consumer loyalty. To test the effect of packaging variables on consumer loyalty by comparing significantly the value of t-count = 2.129 with t- table (n = 100 α = 5%) of 1.661 so that it can be concluded t-count> t- table then hypothesis is accepted which means the packaging has an influence on consumer loyalty. To test the effect of the variable Guarantee on consumer loyalty by comparing significantly the value of t-count = 2.522 with t-table (n = 100 α = 5%) of 1.661 so that it can be concluded t-count > t-table then hypothesis is accepted which means that the Warranty has an influence on consumer loyalty. To test the effect of service variables on consumer loyalty by comparing significantly the value of t-count = 4.387 with t-table (n = 100 α = 5%) of 1.661 so that it can be concluded t-count t> t-table then hypothesis is accepted which means the service has an influence on consumer loyalty